2015
DOI: 10.1016/j.rbmo.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to evaluate a device for the intravaginal culture of embryos

Abstract: The aim of this comparative randomized embryology trial was to determine if an intravaginal culture device (IVC) can provide acceptable embryo development compared with conventional IVF. Ten women between the ages of 27 and 37 years with an indication for IVF treatment were included in this study. After ovarian stimulation, oocytes were randomized to fertilization in the IVC device or using conventional IVF. Fertilization rates were higher in the IVF group compared with the IVC device (68.7% ± 36 % versus 40.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(2015) used ICSI embryos and found comparable Day 3 development and PRs. A pilot RCT of 10 patients showed that fertilization and PRs were higher with conventional IVF treatment as compared to fertilization in the device (CPR: 43% (per patient ET procedure) versus 30% (per cycle)) ( Mitri etal. , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…(2015) used ICSI embryos and found comparable Day 3 development and PRs. A pilot RCT of 10 patients showed that fertilization and PRs were higher with conventional IVF treatment as compared to fertilization in the device (CPR: 43% (per patient ET procedure) versus 30% (per cycle)) ( Mitri etal. , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…By lowering costs, we were able to make assisted reproduction more democratic, reaching more couples with reproductive challenges. Studies carried out in several countries have shown good results using the technique in a three day culture ( Coelho et al, 2013 ; García-Ferreyra et al , 2015 ; Lucena et al , 2012 ; Mitri et al ., 2015 ). The use of the IVC technique in prolonged culture until the 5 th day of the embryo was reported by Doody et al (2016) with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…The application of mild stimulation protocols in a low-resource population and in a primarily fellow operated setting has been shown to result in clinically significant pregnancy rates at significantly reduced costs ( 3 ). Additionally, intravaginal culture is a Food and Drug Administration–approved alternative to the use of traditional embryology laboratory incubators, which could, in some settings, lower costs; however, outcome data for this method are more limited ( 72 , 73 , 74 ). These and other strategies can be implemented by clinical programs operated by residents and/or fellows to help lower financial barriers for patients.…”
Section: Strategies To Improve Barriers In Access To Care Among Train...mentioning
confidence: 99%